Between the player and the spectator: ludic and performative dimensions in theatre education (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article analyzes the relationship between player and spectator within theater teaching-learning processes, exploring play as both an aesthetic and pedagogical device. Based on a theoretical review and an analysis of the influences of contemporary theater on pedagogical practices, it discusses three theatrical modalities—theater game, jeu dramatique, and drama in education—highlighting the centrality of playfulness in fostering critical perception, creative autonomy, and the capacity for relational alterity in both active players and spectators. The study concludes by valuing play not merely as a scenic tool, but as an emancipatory aesthetic activity that promotes critical, sensitive, and open subjectivities—especially in contexts of increasing political and social polarization.
Keywords: player/spectator; playfulness; performative; otherness; theatre pedagogy